2021
DOI: 10.3390/app11031188
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Stresses Due to Weathering in Natural Stones

Abstract: Natural weathering is known as one of the key mechanisms causing degradation in building materials. Great efforts have been made to develop new materials and new processes for protecting those that already exist. Natural stones are an example of a natural material that has been extensively used for building construction since ancient times. In addition, they fit durability, aesthetic, and mechanical requirements. Thus, they still have great importance in the construction business nowadays. Though chemical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Solar radiation is by far the most important heat source in buildings. For this reason, there are several models available to calculate this parameter [14], which have been used [15] to study the sol-air temperature in a natural stone (marble). Following the work of [13], the authors evaluated the induced stress by daily variation of temperature in external façades using a model developed by [16], which is the model that supported the development of the simplified model by [14] for clear-sky radiation.…”
Section: A Energy βAlancementioning
confidence: 99%
See 1 more Smart Citation
“…Solar radiation is by far the most important heat source in buildings. For this reason, there are several models available to calculate this parameter [14], which have been used [15] to study the sol-air temperature in a natural stone (marble). Following the work of [13], the authors evaluated the induced stress by daily variation of temperature in external façades using a model developed by [16], which is the model that supported the development of the simplified model by [14] for clear-sky radiation.…”
Section: A Energy βAlancementioning
confidence: 99%
“…where t 3 is the molar mass of water, > g R7 is the partial pressure of water vapor, and , is the universal gas constant. The partial pressure of water vapor > g R7 is calculated with the relative humidity ,given by: ,-= q k Crs q kz Crs (15) where > g. R7 is the saturation pressure of water vapor. In the present study, this variable is given by Tetens equation, as shown in [23,24]:…”
Section: Mass Concentration Of Water Vapor (Absolute Humidity or O) C...mentioning
confidence: 99%